Microorganisms as a sustainable aquafeed ingredient: a review - Wan-Mohtar, Wan Abd Al Qadr Imad; Ibrahim, Mohamad Faizal; Wan Rasdi, Nadiah; Zainorahim, Norhayati; Mohd Taufek, Norhidayah (Wiley, 2021)
Aquaculture is considered one of the world's fastest-growing food production industries. It provides one of the most environmentally friendly sources of edible protein. The rapid expansion of aquaculture has occurred in response to a huge increase in world population and the corresponding demand for food, highlighting a path towards intensive sustainable products and resource efficiency. Improved process efficiency has fuelled aquaculture expansion, which involves addressing operational performance, particularly on nutrition and health of farmed fish, as well as a trend towards reaching natural or organic certification. Although there is ample evidence to support the use of microorganisms, including algae, bacteria, fungi, archaea, protozoa and viruses, their use in aquaculture nutrition is still limited in natural medicine development and therapies. Notably, various applications of microorganisms feed have a significant impact on aquatic animal health and husbandry. However, there is a need to discuss various roles of microorganisms used in aquaculture feed extensively. This review discusses the potential of microorganisms and their role as value added aquaculture feed, which could offer aquaculture and feed producers considerable benefits.